Método de otimização não-linear para impor PSDs arbitrárias em modems DSL: análise estatística e prática - ABRAHIM, Harney Edison Pereira (Universidade Federal do Pará, 2012)
This work aims to present a method to solve the mapping problem between the theoretical dynamic spectrum management (DSM) solutions and the commercial DSL modems transmitting power spectrum densities (PSDs) parameters. The method uses an integer codi ed genetic algorithm (GA) to solve the problem. The GA is responsible for nding the ttest parameters that represents an arbitrary PSD, under the restrictions imposed by the actual DSL equipments and standards. This work shows a comparative study of the proposed method with another concurrent. A statistics study of the proposed method considering the average, standard deviation and con dence interval is done. Finally, two di erent laboratory setups are presented. One of them to PSD measurement and other to use in transfer function measurements. Both setups can be reused in other works.